THE IMPORTANCE OF ISLAM IN CHILD UPBRINGING - Suyarov Akram Firdavs ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Islam provides a comprehensive and holistic framework for child upbringing, emphasizing the development of moral, spiritual, intellectual, and social dimensions of a child’s life. Through principles derived from the Quran and Hadith, parents are entrusted with the responsibility of nurturing their children into ethical, God-conscious individuals who positively contribute to society. This article explores the multifaceted role of Islamic teachings in child upbringing, focusing on the responsibilities of parents, the role of moral education, the importance of faith and spirituality, and the creation of a supportive home environment. By adhering to Islamic principles, families can foster an environment that nurtures the holistic growth and well-being of their children, ensuring success in both this life and the hereafter.